The alignment argument: at the crossroads between mindfulness and metacognition. (2nd January 2018) - Martínez Ruiz, Xicoténcatl
ABSTRACT: The goal of this article is to identify and discuss the challenges and main problems associated with the interrelations between mindfulness and metacognition, and to provide strategic options for the future to deal with the potential of both in educational scenarios. Two central questions are the guidance: how is it possible to think about thinking? What aspects make a self-reflexive process possible in relation to metacognition and mindfulness? In the first part I analyse key intersections between metacognition and mindfulness. Then I present an overlapping problem as a hypothesis. In the third part of the paper I introduce an argument of self-awareness alignment as an interrelated commonality in mindful and metacognitive practices. I argue from textual evidence of Sanskrit philosophy for a solution on an overlapping problem. I describe significant positive intersections between mindful and metacognitive interventions.